Identifikasi Faktor-Faktor yang Mempengaruhi Pendapatan Petani Asparagus (Kasus pada Kelompok Tani Sayur Mertanadi di Desa Pelaga, Kabupaten Badung) - SUYOGA, K A EDI; DARMAWAN, DWI PUTRA; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.1, Januari 2017DO - 10.24843/JAA.2017.v06.i01.p19, 2017)
Identification of Factors Affecting Asparagus Farmer’s Income (Case On Kelompok Tani Mertanadi at Pelaga Village, Badung Regency) Asparagus is one of the horticultural products that has high sales value. MertanadiVegetables Farmer group is a group of farmers who produce asparagus in Bali. Thepurpose of this study was to determine the factors of production that have an impacton farmer’s income. Data collection for this study was conducted from May to June2016 with accidental sampling method. PLS path modeling is used to analyze theinfluence of production factors on income. Results showed some of the factors ofproduction such as chicken manure, cow manure, NPK fertilizer, and urea fertilizerhas effect on revenue. All factors of production are reflected through latent variablesfertilizers and chemicals, with t-statistics value of 5.625 at 5% significance level andalso with f2 value of 0.552 in the model. Other factors of production used as anindicator obtained did not have a significant effect on revenue. Suggestion can begiven based on this research to farmers is to optimize the use of fertilizers and drugsin the production process by taking into account the costs required. Government isexpected to support the farmers with price support policies. Further research isexpected to do research with indicators relating to cost with more indicators and alarger sample.
Keywords: factors, production, asparagus, farmer’s income